Induction of brain-derived neurotrophic factor in enteric glial cells stimulated by interleukin-1β via a c-Jun N-terminal kinase pathway - Fukumoto, Masanobu (J Clin Biochem Nutr, 2020)
Brain-derived neurotrophic factor exhibits neurotropic and neuroprotective functions and is increased in the colonic mucosa of patients with irritable bowel syndrome in correlation with the severity and frequency of abdominal pain. However, there are no reports of brain-derived neurotrophic factor expression in enteric glial cells. We evaluated the mRNA and protein expressions of brain-derived neurotrophic factor in enteric glial cells and culture medium and levels of mitogen-activated protein kinase after stimulation with interleukin-1β. Brain-derived neurotrophic factor mRNA expression was increased by interleukin-1β (3.125–75 ng/ml) and time-dependently increased 3-fold (24 h) and 4-fold (48 h) by interleukin-1β (50 ng/ml). Pro- and mature brain-derived neurotrophic factor proteins were both significantly increased at 48 h by interleukin-1β. However, the mature form was predominant in the cultured medium. Interleukin-1β increased phosphorylated-p38 mitogen-activated protein kinase expressions 2-fold higher at 5 and 15 min, and also phosphorylated-c-Jun N-terminal kinase expression 5-fold at 5 min and 10-fold at 15 min. Prior treatment with phosphorylated-c-Jun N-terminal kinase inhibitors decreased interleukin-1β-induced brain-derived neurotrophic factor by 50%. Thus, brain-derived neurotrophic factor expression was induced by interleukin-1β in enteric glial cells via a phosphorylated-c-Jun N-terminal kinase pathway, which might affect the enteric nervous system during stress.